Severity of temporomandibular disorders in women: validity and reliability of the Fonseca Anamnestic Index - Campos,Juliana Alvares Duarte Bonini (2014)
The aim of this study was to assess the validity and reliability of the Fonseca Anamnestic Index (IAF), used to assess the severity of temporomandibular disorders, applied to Brazilian women. We used a probabilistic sampling design. The participants were 700 women over 18 years of age, living in the city of Araraquara (SP). The IAF questionnaire was applied by telephone interviews. We conducted Confirmatory Factor Analysis (CFA) using Chi-Square Over Degrees of Freedom (χ2/df), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA) as goodness of fit indices. We calculated the convergent validity, the average variance extracted (AVE) and the composite reliability (CR). Internal consistency was assessed by Cronbach's alpha coefficient (α).The factorial weights of questions 8 and 10 were below the adequate values. Thus, we refined the original model and these questions were excluded. The resulting factorial model showed appropriate goodness of fit to the sample (χ2/df = 3.319, CFI = 0.978, TLI = 0.967, RMSEA = 0.058). The convergent validity (AVE = 0.513, CR = 0.878) and internal consistency (α = 0.745) were adequate. The reduced IAF version showed adequate validity and reliability in a sample of Brazilian women.